Perceptions of Private Market Landlords Who Rent to Tenants of a Housing First Program. Issue 3 (7th April 2015) - Aubry, Tim; Cherner, Rebecca; Ecker, John; Jetté, Jonathan; Rae, Jennifer; Yamin, Stephanie; Sylvestre, John; Bourque, Jimmy; McWilliams, Nancy
Abstract: The rental of housing units by landlords to participants in Housing First (HF) programs is critical to the success of these programs. Therefore, it is important to understand the experiences of landlords with having these individuals as tenants. The paper presents findings of qualitative interviews with 23 landlords who rented to tenants from a HF program located in a small city and adjoining rural area in eastern Canada and in which approximately 75 % of tenants had been housed for at least six consecutive months at 2 years in the program. Findings showed that landlords are motivated to rent to HF tenants for financial and pro‐social reasons. They reported holding a range of positive, neutral, and negative perceptions of these tenants. They identified problems encountered with some HF tenants that included disruptive visitors, conflict with other tenants, constant presence in their apartments, and poor upkeep of units. On the other hand, landlords perceived HF tenants as being mostly good tenants who are similar to their other tenants. Implications for practice in the context of HF programs are discussed.